Migalastat: A Review in Fabry Disease - McCafferty, Emma H. (Drugs, 2019)
Fabry disease is a rare lysosomal disorder characterized by deficient or absent α-galactosidase A activity resulting from mutations in the GLA gene. Migalastat (Galafold™), a pharmacological chaperone, stabilizes and facilitates trafficking of amenable mutant forms of α-galactosidase A enzyme from the endoplasmic reticulum to lysosomes and increases its lysosomal activity. Oral migalastat is the first pharmacological chaperone approved for treating patients [aged ≥ 18 years (USA and Canada) or ≥ 16 years in other countries] with Fabry disease who have a migalastat-amenable GLA mutation. In the FACETS trial in enzyme replacement therapy (ERT)-naive patients with GLA mutations amenable or non-amenable to migalastat, there was no significant difference between the migalastat and placebo groups for the proportion of patients achieving a ≥ 50% reduction in the number of globotriaosylceramide (GL-3) inclusions/kidney interstitial capillary (KIC) at 6 months [primary endpoint; intent-to-treat (ITT) population]. In the modified ITT population (i.e. patients with migalastat-amenable GLA mutations), relative to placebo, migalastat treatment significantly reduced the mean number of GL-3 inclusions/KIC and plasma lyso-globotriaosylsphingosine levels at 6 months. Among evaluable patients, migalastat maintained renal function and reduced cardiac mass after ≤ 24 months’ therapy. In the ATTRACT trial in ERT-experienced patients, renal function was maintained during 18 months of migalastat or ERT; however, migalastat significantly reduced cardiac mass compared with ERT. Migalastat was generally well tolerated in both of these trials. Given its convenient oral regimen and the limited therapeutic options available, migalastat is an important treatment option for Fabry disease in patients with migalastat-amenable GLA mutations.